The epidemiology of dengue outbreaks in 2016 and 2017 in Ouagadougou, Burkina Faso. Issue 7 (July 2020) - Im, Justin; Balasubramanian, Ruchita; Ouedraogo, Moussa; Wandji Nana, Lady Rosny; Mogeni, Ondari D.; Jeon, Hyon Jin; van Pomeren, Tayma; Haselbeck, Andrea; Lim, Jacqueline Kyungah; Prifti, Kristi; Baker, Stephen; Meyer, Christian G.; et al.
Abstract: Background: Dengue is prevalent in as many as 128 countries with more than 100 million clinical episodes reported annually and four billion people estimated to be at risk. While dengue fever is systematically diagnosed in large parts of Asia and South America, the disease burden in Africa is less well investigated. This report describes two consecutive dengue outbreaks in Ouagadougou, Burkina Faso in 2016 and 2017. Methods: Blood samples of febrile patients received at Schiphra laboratory in Ouagadougou, Burkina Faso, were screened for dengue infection using SD Bioline Dengue Duo rapid diagnostic test kits (Standard Diagnostics, Suwon, Republic of Korea). Results: A total of 1, 397 and 1, 882 cases were reported by a single laboratory in 2016 and 2017, respectively. Most cases were at least 15 years of age and the results corroborated reports from WHO indicating the circulation of three dengue virus serotypes in Burkina Faso. Conclusion: This study complements data from other, simultaneously conducted surveillance efforts, and indicates that the dengue disease burden might be underestimated in sub-Saharan African nations. Dengue surveillance should be enhanced in African settings to determine the burden more accurately, and accelerated efforts towards a dengue vaccine should be put in place. Abstract : Viruses; Viral disease; Epidemiology; Public health; Infectious disease; Dengue, Outbreak; Burkina Faso; Serotypes.